Pemanfaatan Fenomena The Bandwagon Effect Pada Generasi Muda Indonesia - Kartika Djuna; Astuti Nur Fadillah (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Social media is one example of the development of the flow of information and technology today. Social media invites anyone to communicate. Teenagers as active social media users tend to have the habit of posting about their daily life activities. From the perspective of teenagers, they assume that the more active they are on social media, the more they will exist and not be out of date. But social media on the other hand also has a negative side. If social media users can't filter information well, sharing private activities will boomerang. The bandwagon effect is a phenomenon that arises from the rapid development of social media, this phenomenon describes a person who tends to follow a trend, ranging from lifestyle, behavior, how to dress, how to talk, or content on social media.Purposes of the Research: The purpose of this research is to analyze and discuss the use of the bandwagon effect phenomenon in Indonesia's young generation.Methods of the Research: The research method used is a secondary research type. The type of secondary research is the method in which information has been collected by the researcher. Newspapers, online communities, reports, audio-visual evidence, etc. included in the category of secondary data.Results of the Research: The younger generation as social media users are accustomed to expressing the desire to feel existent. Currently there are many types of social media that are always used by today's society, such as Facebook, Instagram, TikTok, and so on. Social media has a very big influence on social change in today's young Indonesian generation. One phenomenon that arises from the effects of using social media among the public is the bandwagon effect. Factors that can make someone behave Bandwagon Effect are group thinking, desire to be accepted in a group, and fear of being ostracized. The Bandwagon effect does have a negative effect, but keep in mind that a phenomenon that occurs in society always has positive and negative sides as well as the Bandwagon effect. This phenomenon can also be exploited from an economic point of view. The bandwagon effect can be used by the younger generation to grow the economy independently